Executive Functioning in Criminal Behavior: Differentiating between Types of Crime and Exploring the Relation between Shifting, Inhibition, and Anger. Issue 3 (2nd July 2016) - Seruca, Tânia; Silva, Carlos F.
ABSTRACT: The study of executive functioning in prisoner populations is important to the task of elucidating underlying neuropsychological causes of criminal behavior; these deficits should also be considered in offender rehabilitation efforts. A general sample of offenders ( N = 42), further divided into three subtypes of crimes (violent, property, and drug trafficking), was tested using a battery of executive functioning measures and compared with a group of non-offenders ( N = 28). Offenders performed worse than non-offenders on mental flexibility and planning measures, and pairwise analysis revealed differences in the executive functioning of the offender subgroups – the property offenders had poorer performance on mental flexibility measures, while the violent offenders performed worse on planning measures. The relationship between executive functions and anger in the criminal subgroups was further explored. Preliminary results revealed strong significant correlations between mental flexibility, interference resistance, and anger control in the subgroup of violent offenders. Further investigation of the relation between executive functions and anger in violent offenders is recommended.